Vegetation cover change on Tindfjöll mountains, Iceland, assessed by aerial photographs, topography, and climate - Guðrún Guðjónsdóttir 1973- (2022)
Thesis approved in partial fulfilment of a double Nordic Master MSc degree in environmental changes at higher latitudes (EnCHiL), from Lund University and Agricultural University of Iceland. Department of Physical Geography and Ecosystem Science, Climate change is having a great impact on the fragile High Latitude environment where warming is occurring at a rate at least double the global average. It is urgent to understand the relationship between climate and vegetation cover, which is playing an important role, as a carbon sink, for biodiversity, and for protecting against natural hazards. Less studied but equally important is to understand how mountain areas are responding to climate warming and how topography; elevation, aspect, and slope are affecting vegetation distribution and dynamics. This study focuses on Tindfjöll mountains, Iceland, and compares two transects representing two different aspects (one south facing and one west facing) between the years 2004 and 2019. The results show that vegetation coverage has increased in both areas while for the same period climate warming has been approximately 1°C. This is especially significant for the vegetation class moss heath. The classes glacier and sand/gravel have on the other hand retreated. The south facing transect has shown more significant increase and the vegetation line in the same area has ascended about 150 m during the study period. These results indicate that not only climate is having a significant impact on vegetation production but also topography; elevation, aspect, and slope is creating a microclimate which highly affects vegetation growth. The most important factor is temperature with higher summer temperature and prolonged growing season while warmer winters lead to less protecting snow cover. Aspect and incoming solar radiation are also a strong influencing factor as south facing slopes (more incoming solar radiation) are showing much stronger vegetation responses than west facing slopes. The findings indicate that similar changes ...